Performance decline in a low-stakes test at age 15 and educational attainment at age 25: Cross-country longitudinal evidence. (October 2021) - Borgonovi, F.; Ferrara, A.; Piacentini, M.
Abstract: Introduction: Educational attainment is associated with important life outcomes including labour market performance, health status, well-being, civic and political participation. An important question is whether it is possible to identify early those students who lack the achievement motivation that is needed to complete a higher education degree. Methods: Longitudinal follow-ups of representative samples of participants in the 2000 and 2003 Programme for International Student Assessment (PISA) from Australia, Denmark and Switzerland (N = 3110; 1130; and 1962; age = 15 to 27; % females 51%, 51%, 49%; ethnicity/race unknown) were used to identify the association between a measure of effort on a cognitively demanding low-stake task at age 15 – performance decline during the test – and educational attainment at age 25–27. Results: A one SD difference in performance decline was associated with a 5–6 percentage point difference in the probability of obtaining tertiary-level qualifications ( r  = −0.15 in Australia; −0.11 in Denmark and −0.11 in Switzerland). We find no evidence of differences in this relationship across genders, socio-economic status and baseline levels of ability in the three countries. The association between performance decline and educational attainment is homogeneous across these groups. Self-reported measures of achievement motivation were not predictive of educational attainment in the three countries. Conclusions: Our work contributes new longitudinal evidence to the body of research in education employing behavioural measures of motivation and engagement. It can be used to understand the potential long-term consequences of disparities in students' preparation to sustain effort over cognitively demanding tasks. Highlights: We used longitudinal follow-ups of PISA from Australia, Denmark and Switzerland. We used performance decline in PISA as a behavioural measure of effort at age 15. Educational attainment at age 25 is associated with performance decline at age 15. Associations do not differ by gender, SES and baseline achievement.